2009
DOI: 10.1002/da.20439
|View full text |Cite
|
Sign up to set email alerts
|

Approach-avoidance coping conflict in a sample of burn patients at risk for posttraumatic stress disorder

Abstract: It is concluded that the order of coping skill training can influence treatment outcome, success of coping methods, and overall levels of distress. therefore, training in stabilizing and calming methods should precede training in active processing following stressful life events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…food) would experience greater anxiety than those in the control conditions, consistent with prior research that motivational conflict is associated with anxiety (e.g., Aupperle and Paulus 2010;Fauerbach et al 2009;Gray and McNaughton 2000;Mennin and Fresco 2014). Further, we examined whether motivational conflict would also impact the time course of anxiety.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…food) would experience greater anxiety than those in the control conditions, consistent with prior research that motivational conflict is associated with anxiety (e.g., Aupperle and Paulus 2010;Fauerbach et al 2009;Gray and McNaughton 2000;Mennin and Fresco 2014). Further, we examined whether motivational conflict would also impact the time course of anxiety.…”
Section: Introductionsupporting
confidence: 84%
“…In many cases, motivational conflict results in the generation of anxiety, which, when unregulated, further interferes with conflict resolution, thus leading to a vicious cycle of difficulties enacting instrumental, goal-driven behaviors consistent with our values (e.g., Barlow 2002;Fauerbach et al 2009;Gray and McNaughton 2000;Mennin and Fresco 2014). In fact, it has recently been suggested that ''inherent in the notion of an anxiety disorder is conflict between approach-related drives (e.g., to…”
Section: Introductionmentioning
confidence: 99%
“…Individuals experiencing such growth often report spiritual and philosophical changes, enhanced motivation, and a more positive outlook (Kashdan & Kane, ). Although some research indicate that post‐traumatic growth is primarily a consequence of approach‐based coping, other research, including that of the present authors, suggest that avoidance‐based coping may also offer an avenue for such growth (e.g., Arble & Arnetz, ; Fauerbach et al, ).…”
Section: A Model Of First Responder Coping: An Approach/avoidance Bifmentioning
confidence: 53%
“…A pretrauma history of mental disorders, especially mood and anxiety disorders and conduct disorder, is associated with PTSD. [48][49][50] Personality factors, such as neuroticism 51 and avoidance coping, 52,53 have been shown to be associated with increased risk for PTSD, while extraversion has been shown to be protective. There has been an expanding body of literature on the genetic risk factors associated with the development of PTSD.…”
Section: Risk Factors For Development Of Ptsdmentioning
confidence: 99%